Coping with precarity in the tourism performing arts industry: a case study of China's Wa entertainers. Issue 8 (23rd May 2022) - Yang, Xihao; Round, John; Bao, Jigang
Abstract: This article examines the precarious work experiences and coping tactics of entertainers in China's tourism performing arts (TPAs), who are also tourism labour migrants (TLMs). Focusing on a particular ethnic group, Wa entertainers (WEs), this article aims to highlight how TLMs sustain their careers and fight for decent work. Qualitive methods were applied to investigate entertainers in a neglected sector of the tourism industry. The findings show that entertainers face two main aspects of precarity: labour relations and job attributes. Inspired by the precarious TPA work, WEs develop micro-tactics to resist, namely, they have suitable geographical mobility choices and actively participate in skilling and learning. Thus, WEs become more capacitated to switch smoothly between different jobs to sustain a broader career in tourism-oriented sectors. This article offers critical insights into the capability development of tourism practitioners. It reflects on a vernacular, grassroots redefinition of sustainability with respect to decent work, in which a stable or predictable career pathway may not be the ultimate purpose for grassroots TLMs.